Overview of East Asian Studies in Central and Eastern Europe - Winfried Flüchter; Thomas Heberer; Werner Pascha; Frank Robaschik; Markus Taube (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2003)
The following volume reports the findings of an extensive survey about research in the field of East Asian Studies by scholars in central and eastern Europe. The purpose, methodology and major findings of this investigation are presented in the introduction to the report. Organised into two main parts, the report presents the results of four country visits by Duisburg scholars to eastern and central European institutes involved in research on East Asia and an extensive listing of institutes, scholars and research. Two indexes to the study improve its usability in locating scholars and institutes by East Asian country and disciplinary focus.
Keywords: 330; East Asian studies institutions; research; education; Eastern Europe; Central Europe